Politics in Innovation: Power Relationships in the Mobilization of Support in Developing an Innovation Policy - Bambang Widiyahseno (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2018)
Innovation policy is better understood as a question of the ‘novelty’ of ‘acceptance’ which is characterized by an emphasis on technocracy. Ironically, because of the novelty, the sustainability ofinnovation is not anticipated well, and the ability ofinnovators to bequeath the institutional innovations is barely available. This study intends to reveal the problem. The emphasis on the aspects oftechnocracy in the discussion ofinnovationis not well explored. The problem is examined using the descriptive-exploratory approach with the intentionto excavate and interpret objectively the real conditions against the practices of innovation policy. This study focuses on innovation policy in the field of service permissions in Sragen. Data were taken from interviews among the Governors, bureaucrats,board members and various parties concerned. Data analysis was performed using two methods: triangulation and interpretive.This study argues that in order for policy innovation to be successful, it has to be acceptable and sustainable where innovators must build relationships with various parties. It is further recommended that the form and relation ofthe innovation policy be studied more together with other models of bureaucratic innovation.